Fundamentals of anatomy and physiology workbook : a study guide for nursing and healthcare students - Peate, Ian (Wiley Blackwell, 2017)
"This new workbook is a companion to the textbook Fundamentals of Anatomy & Physiology for Nursing & Healthcare Students, and is designed to help and support you with this subject area, by testing and consolidating your knowledge of biological sciences"--Resumé vydavatele
Keywords: anatomie člověka -- úlohy; fyziologie člověka -- úlohy; human anatomy -- problems, exercises, etc; human physiology -- problems, exercises, etc; pracovní sešity; učebnice; activity books; textbooks